ANALISIS MARKETING MIX 4P’S PADA PENJUALAN KERIPIK PISANG ASKHA JAYA - Muhammad Alfin Azhari; Muhamad Emil Rachman (JISAMAR (Journal of Information System, Applied, Management, Accounting and Research), 2023)
Askha Jaya chip sales were down owing to an incorrect marketing mix. The goal of this study is to discover the aspects involved in applying the 4p marketing mix to Askha Jaya Banana Chips sales and how to boost Askha Jaya Banana Chips sales. This study's analytical approach is SWOT analysis using informants, namely the owners and workers of Askha Jaya. According to the SWOT matrix diagram findings, Askha Jaya Banana Chips are in Quadrant I, where the conditions are highly favorable. Askha Jaya Banana Chips has the chance and strength to capitalize on current possibilities; thus, Askha Jaya Banana Chips must develop a plan that supports aggressive growth strategies in order to increase sales.